Pengaruh Model Pembelajaran Structured Inquiry Berbantuan Virtual Laboratorium Terhadap Pemahaman Konsep Siswa - Febriani, Puput; Dewi, Ika Nurani; Mursali, Saidil (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2026)
This study aims to determine the effect of the structured inquiry learning model assisted by virtual laboratories on students' conceptual understanding at SMP Negeri 1 Maronge. This study uses a quantitative approach using a quasi-experimental method and a pretest-posttest control group design. The population of this study were students of SMPN 1 Maronge, with the research sample consisting of students in grades VIIIA and VIIIC. The sampling technique used was cluster random sampling. The research instrument used was a concept understanding test. Data analysis was carried out using the N-gain test to measure the increase in conceptual understanding, and ANCOVA to test differences between groups. The results showed that the conceptual understanding of students in the experimental class who used structured inquiry learning assisted by virtual laboratories-PhET had an N-Gain value of 0.63 (moderate criteria), while the control class had an n-gain value of 0.54 (moderate criteria). The results of the Ancova test showed a sig value of 0.000 ˂ α = 0.05, indicating a significant difference between the experimental and control groups. Thus, it can be concluded that the structure inquiry learning assisted by virtual laboratory-PhET has a positive effect on improving students' conceptual understanding. The results of this study can be a reference for implementing inquiry-based learning and virtual technology in improving the quality of science learning.